The Transition of the Boyongan Tradition Before the Wedding Procession in Central Java - Taufiqotuzzahro, Azzah Nurin; Alawy, Muhammad Syihabudin (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This research investigates the Boyongan tradition's transition before marriage in Gagakan village, Blora Regency, where the bride stays at the groom's house before the consent of Kabul. This tradition is at odds with Islamic teachings due to the mixing of unrelated men and women in one place. Nevertheless, it continues to be practiced by the community. The study focuses on the historical context and current practices of the Boyongan tradition within the Gagakan village community, as well as the community's understanding of the Boyongan custom in pre-marriage settings. The qualitative research method involves direct interviews with various informants, including participants in the Boyongan tradition, elders, religious leaders, and residents of Gagakan village. Findings from the field data reveal that the Boyongan tradition is believed to safeguard the bride and groom's lives from malevolent forces in the afterlife. The Boyongan rule strictly applies only to the bride and groom, determined by the number of market days, the contract date, and the manner in which the woman enters the house. The practice of the Boyongan tradition has undergone notable transitions. While some members of Gagakan Village still adhere to the tradition, others have made adjustments to align with Islamic principles. These adaptations include limiting the duration of the stay, ensuring separate accommodations, and conducting a religious marriage beforehand. This research sheds light on the dynamics of cultural practices and their intersections with religious beliefs within the Gagakan village community. The findings contribute to a deeper understanding of the Boyongan tradition's historical roots and its contemporary adaptations, providing valuable insights for preserving cultural heritage while respecting religious norms in the context of evolving societal values.